Study of an Exhaust Gas Heat Separation System for the Beet Harvester - A. S. Dorokhov; А. G. Aksenov; A. V. Sibirev; M. A. Mosyakov; N. V. Sazonov (Сельскохозяйственные машины и технологии, 2022)
It was noted that increased soil moisture worsens the quality of harvesting root crops due to a decrease in the completeness of separation. To increase the separating capacity of a slotted cleaner for root crops, it was proposed to improve the heating of the separating surface with hot exhaust gas. (Research purpose) To optimize the design and technological parameters of an exhaust gas heat separation system of the sugar beet harvester power plant. (Materials and methods) Federal Scientific Agroengineering Center VIM developed an exhaust gas heat separation system for harvesting root crops and potatoes in high moisture conditions using the heat of the harvester power plant exhaust gases. The cleaning quality of the separating system of a self-propelled sugar beet harvester was determined under the gradual engine load from 0 to 100 percent of the nominal rated power. The temperature of the exhaust gases was measured with the assumption of changes in the engine load and its effective power. (Results and discussion) The experiment revealed an increase in the completeness of the separation of a root crops heap from 96.0 to 98.8 percent at 26-32 percent soil moisture due to the separation system in the form of a cleaning star, which uses the heat of the engine exhaust gases. The established optimal values of the factors under consideration are as follows: the separating star rotation rate is 21.8 revolutions per minute, the distance between the separating star and the deflector is 128.4 millimeters. (Conclusions) It was determined that the high quality of the technological process of root crops harvesting in high soil moisture conditions ensuring a 97-percent separation efficiency is possible if optimize the separating device design and technological parameters and maintain the separating star rotation rate at 20-22 revolutions per minute and the distance between the separating star and the deflector within 120-140 millimeters. The authors noted the prospects of developing this system and the need for theoretical and experimental studies to improve the design and technological process of the harvester separating system.